Improvement of Sea Surface Height Measurements of HY-2A Satellite Altimeter Using Jason-2. Issue 6 (2nd November 2018) - Cui, Wei; Wang, Wei; Jie, Zhang; Yang, Jungang; Jia, Yongjun
Abstract: HY-2A, which was launched on 16 August 2011, is the Chinese first microwave ocean dynamics environment satellite. Analyses of HY-2A daily sea-level anomaly data and HY-2A–Jason-2 (H-J) dual crossover sea-level anomaly differences show that HY-2A has measurement differences that mainly refer to an orbit error. H-J crossover differences and HY-2A–HY-2A (H-H) crossover differences give an estimate of the HY-2A orbit error. Smoothing cubic-spline functions are then used to obtain a continuous estimation of the HY-2A orbit error over time. On the basis of the simultaneous global minimization of H-J dual crossover differences and H-H crossover differences, the HY-2A observation error is efficiently reduced and height measurement data that are more precise are obtained. Specifically, the range bias/trend of the HY-2A altimeter is removed effectively and the root mean square of H-J crossover sea-level anomaly differences decrease from above 60 cm to 5.64 cm, and the standard deviation of H-J crossover differences decreases from 6.68 to 5.64 cm. Furthermore, the rms and standard deviations of H-H crossover differences both decrease from 7.46 to 6.55 cm. The results show that HY-2A after correction has a measurement accuracy and precision that are comparable to those of Jason-2.